Impact of liver transplantation on the natural history of oculopathy in Portuguese patients with transthyretin (V30M) amyloidosis - Beirão, J.M. (2015)
Purpose: Evaluation of the impact of liver transplantation in the natural history of ocular disorders in familial amyloidotic polyneuropathy (FAP) amyloidosis TTR V30M related (ATTR V30M) patients. Design: A clinical, retrospective and cross-sectional study of 64 Portuguese FAP ATTR V30M patients was carried out between January 2005 and December 2011. Methods: Thirty-two liver transplanted patients (both eyes) aged 39.6–53.8 years old, 32/32 male/female, were paired with an equal number of non-transplanted patients, matching for age, gender, age at onset, disease duration and gender of transmitting parent. Intervention or observation procedure: Routine ophthalmological observation. Main outcome measures: Slit-lamp observation for abnormal conjunctival vessels (ACV), tears break-up time, iris, lens; fundus observation for vitreous, retina and optic disc; Schirmer test. Results: Liver transplantation had no influence on tears break-up time, deposition of amyloid on the iris and retinal amyloid angiopathy. Slight, non-statistically significant protective effects of liver transplantation were noted in the first years for some ocular manifestations (ACV and scalloped iris), except for the abnormal Schirmer test, which was significantly more prevalent in non-transplanted patients’ eyes (81% versus 56%, p = 0.002). On the other hand, deposition of amyloid on the lens, vitreous amyloidosis and glaucoma were apparently more common in transplanted patients. Those differences tended to disappear with time. Conclusions: Ocular manifestations of FAP were not influenced by liver transplantation in a meaningful way. Both transplanted and non-transplanted FAP patients need similar regular follow-up due to long-term risk of serious ocular disease.